Development, calibration, and initial application of a prototypical tapping machine - Formoso, Simeon III (Espasyo : Journal of Philippine Architecture and Allied Arts, 2012)
Structural-borne sound (SBS) is sound transmitted through structural systems of buildings like walls, columns and beams. SBS plays a role in considering comfort and privacy in multi-storey buildings. SBS in buildings is usually characterized using commercial tapping machines which are recommended by ISO standards. In this study, we present a fabricated tapping machine and demonstrate its initial use. Our machine is made from bottom up using available local materials. The hammer system used in the commercial tapping machines is adapted as manually operated. We develop machines with three, five and seven-hammer configurations and compare with actual activities and common equipment to establish the corresponding sound intensities in decibels which a configuration can be used for.